Development and Validation of Women's Satisfaction With Hospital-Based Intrapartum Care Scale in Jordan. (May 2016) - Shaban, Insaf; Mohammad, Khitam; Homer, Caroline
Background: Measuring satisfaction with care during labor is an important way to improve maternity services for women. This study was undertaken to develop an instrument to measure women's satisfaction with intrapartum hospital-based care.Method: A multidimensional instrument was initially developed, using three core aspects identified from the literature. An expert panel was convened to further modify the instrument. Finally, a total of 300 low-risk women who gave birth in the past 2 months were asked to complete the instrument to assess validity and reliability.Findings: The 14-item instrument was found to have content and construct validity as well as a high level of reliability (α = .88).Conclusions: This new instrument is a valid and reliable measure of satisfaction with intrapartum care in a Jordanian setting. The instrument can provide valuable information on the quality of services and on future planning for maternity services.